Overcoming Challenges of Education Sector in Indonesia Through Positive Psychology - Jamalul Muttaqin (Faculty of Psychology Universitas Gadjah Mada, 2021)
Challenges of education sector in Indonesia are complex. Literature on Indonesia education has shown these challenges relate to learners, educators, and administrators. We often see, in certain places such as remote areas, poor management of education system from the quality of to human resources. Consequently, this poor education quality led to student’s low motivation and eventually creating the image of education in Indonesia as appeared dreary. This article aims to discuss positive psychology to contextualize challenges of Indonesia’s education. I argue that positive psychology offers insights of overcoming education challenges that might lead to a more joyful educational process. The study is a literature-based research through critical and comprehensive analysis of the phenomenon of education in Indonesia. This research emphasizes that positive psychology works have a very influential space to help achieving welfare of those involve in the education sector. The result offers few recommendations through finding new methods or models of learning that are pleasing that attempt to motivate students to apply positive psychology to improve their quality of life.